Nano-Formulated Mangosteen (Garcinia Mangostana L.) Peel Extract In DiabeticFracture Healing: A Systematic Review Of VEGF, BMP-2, And TGF-Β Modulation - Rofik Adnan; Yuriz Bakthiar; M I Widiastuti (Universitas Negeri Semarang, 2026)
Background: Diabetic fracture healing is often impaired due to disrupted angiogenesis and osteogenesis, necessitating multi-target therapeutic strategies. This study aims to evaluate the effect of nano-formulated mangosteen (Garcinia mangostana L.) peel extract on VEGF, BMP-2, and TGF-β modulation through a systematic literature review.Method: This research employed a systematic literature review design following PRISMA guidelines, with studies retrieved from Scopus and Google Scholar databases. The research variables included mangosteen-derived bioactive compounds, nano-formulation strategies, and key biomarkers (VEGF, BMP-2, TGF-β). Data were collected using predefined inclusion criteria and analyzed qualitatively through thematic synthesis.Results: The results indicate that mangosteen bioactives exhibit significant anti-inflammatory and antioxidant effects, which contribute to the upregulation of VEGF expression and enhancement of BMP-2 and TGF-β signaling, thereby promoting angiogenesis and osteogenesis. Nano-formulation further improves bioavailability, stability, and targeted delivery, resulting in a synergistic therapeutic effect in diabetic fracture healing.Conclution: In conclusion, nano-formulated mangosteen demonstrates strong potential as a multi-target regenerative therapy; however, further clinical studies are required to confirm its efficacy and safety in human subjects.